PENGARUH PEMBERIAN TABLET ZAT BESI DAN VITAMIN C TERHADAP KENAIKAN KADAR HEMOGLOBIN PADA IBU HAMIL ANEMIA - Anjar Junia Puspita (Yayasan Pendidikan Medika Indonesia, 2021)
Anemia is a nutritional problem in the world that often occurs in pregnant women. In Indonesia, the prevalence of anemia in pregnant women in 2018 reached 48.9%. Anemia in pregnancy occurs due to increased oxygen demand by the fetus, causing an increase in blood volume greater than the number of erythrocytes, resulting in blood thinning which causes hemoglobin levels <11 g/dl. In reducing the prevalence of anemia in pregnant women, the government carried out a prevention program in the form of giving 90 iron tablets during pregnancy. Vitamin C acts as a pro-oxidant with its ability to reduce ferric (Fe3+) through the binding of complex formation followed by the formation of ferrous (Fe2+) with increasing the absorption of non-heme iron in the proximal duodenum. This research was conducted through a literature study method with the aim of knowing whether the combination of giving iron (Fe) and vitamin C tablets can increase hemoglobin levels in pregnant women. The results of the literature study showed that there was an effect of giving iron (Fe) and Vitamin C tablets to pregnant women on increasing hemoglobin levels. Keywords: Anemia; Hemoglobin; iron tablets; Vitamin C